2017
DOI: 10.1177/1687814017732892
|View full text |Cite
|
Sign up to set email alerts
|

A research into the flow and vortex structures around vehicles during overtaking maneuver with lift force included

Abstract: A simulation model of overtaking maneuvers is established to research into the flow and vortex structures around two identical Ahmed vehicles. The simulation demonstrates how the flow and vortex structures generate and change, which influences the aerodynamical coefficients of the vehicles most. In this study, a transient solver is used on the platform of ANSYS/Fluent, and the sliding mesh method is adopted to simulate the motion of the overtaking vehicle, which realizes a more actual recovery of the road cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The wind pressure coefficient of the model is unaffected by the overtaking behavior. By combining the pressure contour and the isosurface of velocity in Shao et al [27], the two vehicles do not interfere with each other when their lateral distance is far enough. For the experiments in this section, the two vehicles are separated by one lane, and their lateral spacing is significantly large.…”
Section: Influence Of Overtaking Lanesmentioning
confidence: 99%
See 2 more Smart Citations
“…The wind pressure coefficient of the model is unaffected by the overtaking behavior. By combining the pressure contour and the isosurface of velocity in Shao et al [27], the two vehicles do not interfere with each other when their lateral distance is far enough. For the experiments in this section, the two vehicles are separated by one lane, and their lateral spacing is significantly large.…”
Section: Influence Of Overtaking Lanesmentioning
confidence: 99%
“…Howell et al [26] found that a small lateral distance increases the peak value of each aerodynamic parameter. In addition, different relative velocities also have varying effects on the flow field around two vehicles [27]. Furthermore, the relative velocity does not affect the trends of the aerodynamic coefficient curves of two vehicles, but it can affect their peak value [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overtaking process has been extensively studied using numerical modeling. Clarke and Filippone, 12 Uystepruyst and Krajnovic, 13 and Shao et al 14 simulated the overtaking process for two car models to determine the effect of lateral separation and relative speed for two models on the aerodynamic forces that act on them. The results show that there is increased interference between the aerodynamic forces that act on the vehicle models as the lateral separation decreases and/or the relative velocity between the two vehicle models increases during the overtaking process.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the computational resource that is required for a simulation, most numerical studies of the overtaking process use two-equation Reynolds-averaged Navier-Stokes equation (RANS) models, which are, to a certain degree, reliable and economic turbulence models. These include the standard k ε model, 12 the RNG k ε model, 12,16 the realizable k ε model, 14 the SST k ω model, 12,2022 the ζ f model 13 and the low-Reynolds-number k ε model. 20 The SST k ω model 12,20,22 gives an accurate prediction of the aerodynamic characteristics among these RANS models because it predicts near-wall flow behavior if there is an appropriate design for the near-wall grid mesh.…”
Section: Introductionmentioning
confidence: 99%